Comparative transcriptomics to reveal the mechanism of enhanced catalytic activities of Aspergillus niger whole-cells cultured with different inducers in hydrolysis of citrus flavonoids. (June 2022) - Zou, Yucong; Li, Xiaofeng; Xin, Xuan; Xu, Haixia; Mo, Lan; Yu, Yigang; Zhao, Guanglei
Graphical abstract: Highlights: A novel whole-cell catalytic hydrolysis of citrus flavonoid glycosides is presented. The type of inducer has decisive influence on biosynthesis of intracellular enzymes. Transcriptome is applied to reveal the mechanism of whole-cell catalytic hydrolysis. Rhamnosidase and glucosidase are co-induced and sequentially catalyze hydrolysis. Abstract: A new Aspergillus niger whole-cell catalyst was cultured for the cascade hydrolysis of hesperidin (HES) to produce high-value hesperetin-7-O-glucoside (HG) and hesperetin with high conversion (above 90%). Moreover, the inducers used were shown to be useful for cell growth and to induce cells to produce specific enzymes. Remarkably, the type of inducers determined whether the cells can hydrolyze HES. The product composition was also controllable by adjusting different inducers. Transcriptome analysis suggested that both naringin-vs-blank group and saccharose-vs-blank group had obviously difference in gene expression. The naringin-vs-blank group was mainly up-regulated differentially expressed genes (DEGs), while saccharose-vs-blank group was mainly down-regulated DEGs. The Gene Ontology (GO) analysis showed that whether naringin or saccharose was added as an inducer would greatly affect the catalytic activity of cells. Furthermore, 3 genes related to rhamnosidase, 14 genes related to glucosidase and 5 genes related to hydrolase activity were found. These genes were not only involved in rhamnosidase and glucosidase activities, but also spliceosome and the sucrose and starch metabolic pathways. The quantitative real-time polymerase chain reaction (qRT-PCR) analysis indicated that the results of transcriptome sequencing were reliable. This study gave a new approach to hydrolyze HES, and new perspectives to understand the mechanisms associated with the hydrolysis of whole-cell catalyst.